FACTORS RELATED WOMENS AGE KNOWLEDGE WHO HAS BEEN MARRIED ABOUT THE INTRA UTERIN (IUD) PLASENTA POST DEVICE IN THE WORKING AREA OF PUSKESMAS INDRAPURI IN 2017 - Husna, Asmaul (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
According to Banda Aceh City Health Office (2014) the number of active KB participants in Banda Aceh is 30,047 people, widely used contraceptive methods are 16,562 injections (39.08%), 11.29 pills (26.03%), condoms 1,617 (3, 82%), IUD / spiral 642 (1.51%), implant 192 (0.453%), MOW 4 (0.01%), and MOP (0.002%). The purpose of this research is to recognize factors related to knowledge of woman of child-bearing age (WUS) about intra uterine device (IUD) post placenta in working area of Puskesmas Indrapuri year 2017. Population in this research are all married women age group (WUS) Indrapuri Puskesmas working area of 208 people After the calculation as above, then got the result of sample at least counted 68 people. While for sampling technique used Random Sampling technique that is random sampling. This research has been conducted in Indrapuri Health Center working area in July of 2017. The result of bivariate analysis has a significant correlation between education and information about Knowledge of Married Age Fertile Women About Post Placenta IUD in Puskesmas Indrapuri Working Area, Regency of Aceh Besar Year 2017. Conclusion Based on the results of research that has been done then the research can collect the results of the research as follows There is a meaningful relationship between education with knowledge of women of reproductive age who are married about post placenta IUD in the work area of Puskesmas Indrapuri Regency of Aceh Besar Year 2017 with p = 0.001 (Î± = 0.05). There is a significant correlation between information from health personnel and knowledge of married women of post-fertile age of IUD post placenta in Indrapuri Regency of Aceh Besar working area of 2017 with p = 0.001 (Î± = 0.05). Suggestion is expected to the place of research to participate actively in giving counseling about contraception tool especially the use of Post Placenta IUD in case of unexpected event can be handled with appropriate action, and can give information about mother and child health which can be used as benchmark for health mother and child.Keywords: Education, information, IUD